Engenharias, Ciência E Tecnologia 7 2019
DOI: 10.22533/at.ed.93319310119
|View full text |Cite
|
Sign up to set email alerts
|

Uma Abordagem Alternativa Do Conteúdo De Ácidos E Bases Em Um Curso De Nivel Técnico Subsequente

Abstract: DOI O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. 2019 Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The universal indicators used are: bromothymol blue, methyl orange, phenolphthalein and litmus paper. However, there are some compounds present in vegetables that can be used as acid-base indicators (Ferreira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The universal indicators used are: bromothymol blue, methyl orange, phenolphthalein and litmus paper. However, there are some compounds present in vegetables that can be used as acid-base indicators (Ferreira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The natural indicators are pigments such as anthocyanins taken from vegetables, such as red cabbage (Ferreira, 2016), beet (Martins et al 2017), red onion (Santos, 2017), black beans (Pereira, 2017), turmeric (Silva et al 2018), flowers such as red or pink hibiscus (Ávila, 2015), Roselle Hibiscus sabdariffa L. (Nuryanti et al 2013), also fruits such as plum (Borges et al, 2014) and grape (Terci & Rossi, 2002), as shown in Table 1, have both a different color in acidic, basic and neutral media.…”
Section: Introductionmentioning
confidence: 99%